Impaired osteogenic differentiation and enhanced cellular receptor of advanced glycation end products sensitivity in patients with type 2 diabetes - Mattabhorn Phimphilai (2018)
© 2016, The Japanese Society for Bone and Mineral Research and Springer Japan. Preclinical studies have demonstrated impaired osteoblast differentiation in type 2 diabetes (T2DM), which is related to skeletal accumulation of advanced glycation end products (AGEs). However, the role of AGE in osteoblast differentiation in patients with T2DM is unclear. This cross-sectional study was performed to investigate osteoblast differentiation and its association with serum pentosidine and soluble receptor of AGEs (sRAGE). Twenty-seven patients with T2DM and 15 age-matched controls were included to measure sRAGE and osteogenic differentiation in mononuclear cells derived from peripheral blood. The mononuclear cells isolated from patients with T2DM showed a significantly lower rate of osteogenic differentiation (7.4% vs 86.7%, p < 0.0001) with a lower level of ALPL, COL1A1, and BGLAP expression than those of controls by 11-, 44-, and 15-fold respectively, together with nonvisualized mineralization by alizarin red S staining. The levels of pentosidine and sRAGE were comparable in both groups. AGER expression was significantly higher in the T2DM group. BAX expression was also significantly higher in the T2DM group, and showed a strong correlation with AGER expression (r = 0.86, p < 0.0001). Fasting plasma glucose (FPG) level, AGER expression, and BAX expression showed a strong correlation with osteogenic differentiation defects on univariate analysis. However, only FPG showed a correlation with this defect in a multivariate analysis. In conclusion, patients with T2DM showed impairment of osteoblast differentiation, and FPG was an independent risk factor for this impairment. Moreover, T2DM showed a higher cellular sensitivity for activation of receptor of AGEs and higher cellular apoptosis, which may contribute to the defect in osteoblast differentiation.